Developing Angklung Learning Resources to Foster Student Creativity - A Wathon (YASIN, 2026)
The cultivation of creativity stands as a paramount objective in contemporary education, particularly in an era demanding innovative problem-solving and adaptive thinking. While traditional music education often emphasizes technical proficiency, the potential of cultural instruments like the Angklung to serve as a conduit for creative expression remains underexplored in terms of dedicated learning resources. This study, employing a library research methodology, aims to systematically review existing literature to identify key components and pedagogical approaches for developing Angklung learning resources specifically designed to enhance student creativity. The research synthesizes insights from creativity theories, music pedagogy, and educational technology to propose a comprehensive framework. Results indicate that effective resources must integrate elements of open-ended exploration, collaborative learning, digital engagement, and culturally responsive instruction. The findings suggest that a holistic approach, moving beyond rote learning, can significantly unlock students' creative potential through Angklung. This research contributes theoretically by bridging creativity frameworks with cultural music pedagogy and offers practical implications for educators and curriculum developers in designing engaging and creativity-focused Angklung learning environments. The study concludes by emphasizing the critical role of culturally relevant musical instruments in fostering diverse forms of creativity and recommends empirical validation of the proposed resource framework.